The Reaffirmation of Self? Narrative Inquiry for Researching Violence Against Women and Stigma - Ballantine, Carol (Violence against women, 2022)
Stigma presents specific ethical and epistemological problems for qualitative researchers of violence against women. Narrative research methods promise to enable ethical research on violence while still offering deep insight into stigmatized topics. This article describes narrative methods used in six focus group discussions and four in-depth interviews with victim-survivors of violence against women, all African migrant women living in Ireland. The article connects narrative and stigma in research with the social lives of participants. It concludes with specific recommendations for creative uses of narrative inquiry to explore stigmatized themes, noting that stigma can never be entirely removed from the research encounter.